Art, Transformation and the Social Imaginary. Issue 7 (3rd October 2022) - Waddock, Sandra
Abstract: Art uses images, symbols, ideas, and other expressions to enable people to construct new social imaginaries that can inspire change toward a more desirable future. Artists serve as 'seers' of reality as it is, in ways that others do not see, and of what might be. Art can help frame and envision new cultural mythologies and social imaginaries. The 'soft' power of art can change perspectives, raise awareness, and foster socio-cultural change. Art's soft power potentially provides an approach to system transformation more amenable to some than 'hard' power because it taps the holistic right brain's both/and approach to system transformation.